Generation Z sexual activity - Polikarpov, Vladimir A.; Mikhailovich, Kirill S.; Lichko, Maxim H. (Journal of the Belarusian State University. Sociology, 2020)
It has been established that there is a tendency for generation Z to refuse sex. Based on a representative sociological research, it is proved that the percentage of people who distance themselves from sex is growing. The reason for this phenomenon is disclosed. The laws of maintaining the demographic optimum of the population manifest themselves in it. Dependent on population density factors regulate the population and ensure its balance.